Insight into molecular interactions between condensed aromatics in high-temperature coal tar and organic solvents by combining experimental, density functional theory, and molecular dynamics. (15th September 2021) - Yan, Wei-Wei; Wei, Xian-Yong; Li, Jun; Ma, Zhi-Hao; Liu, Guang-Hui; Zhang, Yang-Yang; Li, Zhi-Xin; Wang, Meng-Xiao; Zong, Zhi-Min; Wang, Bao-Jun
Graphical abstract: Highlights: Kilogram-level extraction plant, self-modified HPPC and FPC were used. HBs, X-H···π, >CO···π, π-π stacking, and VDWFs are the main interactions in HTCT. Condensed aromatics with different ARs and heteroatoms were enriched, respectively. The differences in SFE among different condensed aromatics can be illustrated by NCI. Abstract: Kilogram-level extraction, modified high-pressure preparative chromatography (MHPPC), and flash preparative chromatography (FPC) were applied to separate condensed arenes (CAs) and heteroatom-containing aromatics (HACAs) from a high-temperature coal tar and its petroleum ether-extractable portion (PEEP). A series of CAs and HACAs were enriched from PEEP via MHPPC. Naphthalene and other 8 arenes were purified with purities of 99.9% and higher than 75%, respectively, by recrystallization and FPC. Density functional theory and molecular dynamics were used to calculate the solvation free energies (SFEs) and the complex intermolecular interactions (IMIAs), respectively, between solvent and solute at the molecular level. The difference in SFE is positively correlated with the number of aromatic rings of each compound. The IMIAs related to the separations include hydrogen bonds, such as >CH2 ···X (X denotes NH<, –N<, or HO-AR), >CO···X, and –O–H···X bonds, >CH2 ··· π, >CO··· π, –O–H··· π bonds, π···π stacking, and van der Waals forces.